Karakterisasi dan Potensi Acremonium sp. Secara In Vitro Terhadap Cendawan Patogen Fusarium oxysporum: Characterization and Potential of Acremonium sp. Against Pathogenic Fungi Fusarium oxysporum In Vitro - Irvanto, David; Listiyowati, Sri (Departemen Biologi, Institut Pertanian Bogor, 2024)
Various natural interactions exist between fungi and plants, including mutualism and pathogenesis. This study evaluated the interaction of fungi Acremonium sp. to plants and pathogenic fungi. Acremonium sp. was isolated from the root tissue of an oil palm plant using surface sterilization methods before isolation. The potential pathogenicity interaction of Acremonium sp. was assayed towards Chinese white cabbage (Brassica rapa L. var. pekinensis) in vitro. Based on the PDA medium assay, isolated Acremonium sp. exhibited pathogenic traits against Chinese white cabbage within 14 days post-inoculation. Interestingly, Acremonium sp. showed antifungal activity against Fusarium oxysporum IPBCC.19.1468, with an average inhibition rate of 69.11%. Our data suggest the pathogenicity interaction of Acremonium sp. toward cabbage plant and fungi F. oxysporum IPBCC.19.1468.